CSP650: Project / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
This course will enable the students to experience the planning, analysis, design and development phases in handling information technology project. The student develops solutions based on the formulated problem. Students should be able to compile, analyse and present the project carried out in the form of a thesis. Students also should be able to communicate the project outcome effectively through oral and poster presentation.